The Gamification Influence as Marketing Medium on Intrinsic Motivation, Positive Emotion, Customer Engagement and Repurchase Intention - Husnul Habib, H Muhammad; Hidayat, Kadarisman; Kholid Mawardi, Mukhammad (FIA UB, 2023)
Since its launch, PT Tokopedia has been one of Indonesia's digital marketplaces that have rapidly expanded with its Gamification reward technique to promote sales. The researchers intend to measure the gamification method carried out by Tokopedia to its customers. This study aims to investigate the impact of Gamification on intrinsic motivation, positive emotion, and customer engagement. This study also examines the effect of Positive Emotion on the Repurchase Intention variable and the Gamification effect on the Repurchase Intention variable. This study employed descriptive-quantitative explanatory research as the research design and Self-determination theory as the framework of this research. The population in this study were Indonesian citizens with a minimum age of 17 years. Two hundred thirty respondents were collected as the sample through E-Questionnaires distributions. The structural Equation Model using the Variances Based SEM approach, well-known as Partial Least Square (PLS) framework, is employed in this study. The results reveal that Gamification has a positive and significant effect on intrinsic motivation, positive emotions, customer engagement, and repurchase intention.